A covenant of creatures : Levinas's philosophy of Judaism - Fagenblat, Michael (Cultural memory in the present., 2010)
Rejecting the distinction Levinas asserted between Judaism and philosophy, this book reads his philosophical works, Totality and Infinity and Otherwise than Being through the prism of Judaic texts and ideas.